PENERAPAN MEDIA ANIMASI PADA MATERI BANGUN DATAR SEGIEMPAT DALAM PEMBELAJARAN MATEMATIKA KELAS VII SMP: The Application Of Animation Media On Tetragon In Mathematics Learning Of Grade Vii In Junior High School - Nasir, A.Muhajir; Upu, Hamzah; Ihsan, Hisyam (Jurnal Ilmiah Ecosystem, 2016)
The study aimed at discovering the use of animation media on Mathematics learning at Islamic School (MTs.) Paitana Jeneponto which covered the description on students’ activities, students’ responses, and the improvement of learning outcomes. The type of the study was quantitative research, with One Group Pretest-Posttest Design. The population were students of grade VII at MTs. Paitana. The sample of the study were 24 students, selected randomly with assumption that all of the classes of grade VII were homogen in terms of learnin outcomes as the experiment class. Data were collected by using observation sheets of students’ activities, students’ responses, and the test of learning outcomes. Requirement test for analysis used test of normality. Data were analyzed by employing one sample t-test technique. The result of the study revealed that (1) the impact of the use of animation media toward students’ activities are described as follows: in general, students tend to pay attention on the animation media without other irrelevant activities of the lesson and the students’ activities overall was in ideal category; (2) students give positive responses on learning proved more than 80% or all of the questions received positive responses to more than 50% students; (3) the mean score of students’ pretest was 28.79 with the standard of deviation 10.118 from each of the ideal score 100. The gain score was 0.71 from learning outcomes data which was categorized as high, data were distributed normally with the level of significance 0.269 for normalized gain data. By the t-test, the significance value obtained 0.000 meaning that there was improvement on students’ learning outcomes in studying Mathematics after the students taught by employing direct learning model using animation media. The final test indicated as well that 22 out of 24 students (91.67%) achieved the KKM score on Mathematics learning at MTs. Paitana.